2021
DOI: 10.11118/ejobsat.2021.002
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Financing, Agricultural Output Growth and Employment Generation in Nigeria

Abstract: This study investigates the impact of agricultural financing and agricultural output growth on employment generation in Nigeria from 1981 to 2017. The study adopts the framework of the Auto Regressive Distributed Lag (ARDL) Model for analysis. The empirical results show that while agricultural financing increases employment generation in both the short run and long run, the lag of agricultural output growth increases employment generation mainly in the short run. Other variables found to have significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…Also, formal credit social safety net generated some consequences that led to income reversals for rural households. Orji et al (2020) evaluated the causal relationship between agricultural credit and Nigerian agricultural output based on Pairwise Granger causality test. The results indicated that causation between agricultural financing and agricultural output did not exist.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Also, formal credit social safety net generated some consequences that led to income reversals for rural households. Orji et al (2020) evaluated the causal relationship between agricultural credit and Nigerian agricultural output based on Pairwise Granger causality test. The results indicated that causation between agricultural financing and agricultural output did not exist.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…These results imply that the CIS currencies offering a significant interest differential tend, on average, to depreciate over the sample period as UIP predicts. Orji et al (2013) examined whether the theory of UIP holds between Nigeria and USA. The result revealed that the theory of UIP does not hold between Nigeria and USA.…”
Section: Uncovered Interest Rate Parity (Uip)mentioning
confidence: 99%
“…Likewise, Bidisha et al (2018) employing household level and plot-level data for Bangladesh asserted that farm credit has no direct impact on productivity. Further, Orji et al (2020) also evaluating the causal relationship between agricultural credit and Nigerian agricultural output based on pairwise Granger causality test indicated that causation between agricultural financing and agricultural output did not exist. Of late, Sekyi et al (2021) using the United States Agency for International Development (USAID)/FTF survey for 2,903 farm households of Northern Savannah Ecological Zone found a negative but insignificant effect of access to credit on the productivity of high-value crops (i.e.…”
Section: Empirical Nexus Between Agricultural Credit and Crop Product...mentioning
confidence: 99%
“…(2018) employing household level and plot-level data for Bangladesh asserted that farm credit has no direct impact on productivity. Further, Orji et al. (2020) also evaluating the causal relationship between agricultural credit and Nigerian agricultural output based on pairwise Granger causality test indicated that causation between agricultural financing and agricultural output did not exist.…”
Section: Empirical Nexus Between Agricultural Credit and Crop Product...mentioning
confidence: 99%